Morphometric study of Lola Rochia nilotica (Linnaeus 1767) shells from natural harvest found in Indonesian - NATHANIA DINAR WAHYUDI; DEWI HIDAYATI; UCU YANU ARBI; ASMIDA ISMAIL (Society for Indonesian Biodiversity, 2023)
Abstract. Wahyudi ND, Hidayati D, Arbi UY, Ismail A. 2023. Morphometric study of Lola Rochia nilotica (Linnaeus 1767) shells from natural harvest found in Indonesian. Biodiversitas 24: 4711-4722. The population of Rochia nilotica or Lola snails is declining due to shell exploitation for industry, which requires monitoring. The government has implemented a policy to determine R. nilotica regulated on a restricted basis depending on the number (quota) and size of the shell (diameter) with a standard width of 80 cm. Based on the morphometric compositions and size trends of shells, this study aimed to map the potential trade of R. nilotica in Indonesia using the percentage of calculated morphometric data, including Sumatra, Sulawesi, Maluku-East Nusa Tenggara (NTT), and Papua. Morphometric analysis was carried out using caliper parameters of length, width, weight, and the data distribution of morphometrics using descriptive statistics. The results revealed fluctuating yearly data. Good quality of shell size (?80 mm) found from Sumatra (length = 95.13-104.49 mm; width = 86.61-103.46 mm; weight = 172.21-321.96 gram), Malulu-East Nusa Tenggara (NTT) (length = 91.26-106.72 mm; width = 86.53-108.73 mm; weight = 228.01-365.62 gram), Sulawesi (length = 86.92-99.1 mm; width = 84.31-96.25 mm; weight = 205.39-317.33 gram), and Papua (length = 82.46-99.58 mm; width = 76.49-101.24 mm; weight = 182.57-283.07 gram) respectively. Among 909 samples of R. nilotica observed, 89% had a standard width (?80mm), indicating potential mapping of Sumatra (33%), Maluku-East Nusa Tenggara (NTT) (24%), Sulawesi (18%), and Papua (14%). In Sumatra (1.65%), Maluku-East Nusa Tenggara (NTT) (0.9%), Sulawesi (5.6%), and Papua (3.19%), non-standard width shells were sized at 51.46-72.15 mm, respectively. In total, 53.9% of protoconchs were classified as damaged. From 2014-2020, morphological observations of R. nilotica shells traded in Indonesia fluctuated but met the standard size. It is critical to continue monitoring the population and trade of R. nilotica, and the study findings can be used to make catch quota recommendations for the Ministry of Environment and Forestry.